EVALUASI KEMANDIRIAN DAERAH DALAM PENGELOLAAN KEUANGAN DAERAH (STUDI PADA PEMERINTAH KOTA KENDARI) - Haerani, Haerani; Rimporok, Christian; Tamburaka, Sulvariany (JURNAL AKUNTANSI, 2016)
This research aims to determine the level of financial independence to thereception area of the original income of Kendari City by comparing the transfer offunds from the central government. Data was collected by interviews anddocumentation. The analytical method used is ratio analysis method. Equipmentused in the study is the Regional Independence RatioThe results of this study showed that the ratio of local governmentKendari City already does not depend kepaada transfer funds from the provinceduring the period 2012 to 2013. It can be concluded that the independence of theregional government of Kendari in meeting the funding requirements to performthe duties of governance, development, and social service to the community hasbeen very high and even increased year by year, from 111% in 2012 to 112% in2013. This means that the governments dependence on equalization fundKendari City center is already very low.Keywords: Independence Regional, Local Revenue Receipts, and FundBalance/Funds Transfer